2018
DOI: 10.1186/s40657-017-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of francolins (Francolinus, Dendroperdix, Peliperdix and Scleroptila) and spurfowls (Pternistis) based on chick plumage (Galliformes: Phasianidae)

Abstract: Background: This paper describes the chick plumage of spurfowl (Pternistis) and francolin (Francolinus, Dendroperdix, Peliperdix and Scleroptila) chicks, tests its significance for phylogenetic relationships and also explores the patterns of character evolution in the francolin and spurfowl lineages. Previously regarded as monophyletic, the two evolutionarily distant clades are now divided into five genera. Questions considered were whether chick plumage supports the dichotomy between spurfowls and francolins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…All the playbacks were conducted in either the early morning or the late afternoon, except in Decemberthe height of the breeding seasonwhen paired males were reluctant to respond, possibly fearing intruder interference with pair formation (Van Niekerk 2010, Van Niekerk & Mandiwana-Neudani 2018. Responses were recorded when playbacks solicited a male reaction, as a previous study (Van Niekerk 2010) found that males always responded with a salvo and often approached the sound device.…”
Section: Playback Experimentsmentioning
confidence: 99%
“…All the playbacks were conducted in either the early morning or the late afternoon, except in Decemberthe height of the breeding seasonwhen paired males were reluctant to respond, possibly fearing intruder interference with pair formation (Van Niekerk 2010, Van Niekerk & Mandiwana-Neudani 2018. Responses were recorded when playbacks solicited a male reaction, as a previous study (Van Niekerk 2010) found that males always responded with a salvo and often approached the sound device.…”
Section: Playback Experimentsmentioning
confidence: 99%
“…Post-Hall' analyses of francolin/spurfowl syringeal morphology [15], chick plumage [2,9,16], vocalizations [17,18] and DNA [19,20] decisively reject a sister relationship between Hall's two clades of 'francolins' [sensu 2]. A consensus from the above studies is to recommend phylogenetically placing somewhat modified versions of the Hall francolin and spurfowl taxa within two evolutionarily distantly related phasianine lineages, aligned with the now monophyletic Gallinae and Coturnicinae [20].…”
Section: Acentrortyxmentioning
confidence: 99%